The Development and Validation of the Cultural Pluralism Perception Scale (CPPS) - Lalita, Lalita (International Journal of Educational Research Excellence, 2025)
Cultural pluralism is the co-existence of subcultures with a dominant culture while maintaining their identity. India’s higher education institutions offer a diverse learning environment due to this cultural pluralism, impacting student behavior based on their perceptions of these environments. Understanding students’ perceptions of cultural pluralism is therefore crucial. This study aim to develop a scale to measure students’ perceptions of cultural pluralism in higher education. Scale development involved item generation, expert validation, and pilot testing. The framework was drawn from Deardorff’s Intercultural Competence Model (2006) and Chen and Starosta’s Intercultural Communication Competence Model (1996). Initially, 128 items were generated, based on a literature review for content validity. The expert evaluation reduced these items to 47 items on a five-point Likert scale. Purposive sampling was used to select 152 undergraduate students from various departments at Panjab University, Chandigarh, India. The final scale had a three-factor structure with 21 items, validated through explanatory and confirmatory factor analyses. The scale proved reliable, with a Cronbach’s alpha of greater than .70. Overall, this study contributes to the existing knowledge by providing a comprehensive and empirically validated instrument for assessing students’ perceptions of cultural pluralism within academic settings.